Risk Factor for H.Pylori Infection in Children - A.E. Abaturov; O.N. Gerasymenko (Zaslavsky O.Yu., 2014)
Background. The aim of this study was determine the prognostic value of medical, biological and socio-hygienic factors in the formation of H.pylori infection in children. Methods. 283 children aged 7 to 17 years with chronic gastroduodenal pathology in the acute stage were observed. Patients were divided into two groups depending on the presence of H.pylori. The main group included 224 (79.1 %) patients with H.pylori-positive status, control group included 59 (20.9 %) patients who had H.pylori-negative status. Results. Тhe article presents the basic medical and biological and socio-hygienic risk factors in the formation of H. pylori infection in children. With the help of mathematical program processed 145 parameters, including biomedical, social and health indicators of child development in the prenatal and postnatal periods, the clinical manifestations of chronic gastroduodenal pathology, which allowed identifying the main bio-medical and socio-hygienic risk factors of high significance (relative risk > 2.0). We have found out an association of genetic risk factors in the development of H.pylori infection in children in accordance with polymorphisms ASP299GLY of gene Toll-like receptor 4. We have determined the basic clinical and endoscopic features of chronic gastroduodenal pathology in children with H.pylori-positive status and their informational value.